Research Submission: Evolution of Migraine After a 10-Year Follow-Up - Nachit-Ouinekh, Fatima; Dartigues, Jean-Francois; Chrysostome, Virginie; Henry, Patrick; Sourgen, Christophe; El Hasnaoui, Abdelkader (Headache, 2005)
ObjectiveTo assess the evolution of headaches in a workplace cohort over a 10-year period. BackgroundMigraine headaches are associated with significant handicap in everyday activities and poor quality of life. The prevalence of migraine shows a bell-shaped age distribution with a peak during the third and fourth decades. However, there is little longitudinal data available on the natural history of this condition. A prospective health survey undertaken in a large workplace cohort since 1989 provides an opportunity to assess the evolution of migraine and other headache syndromes over a 10-year period. MethodsA sample of 2500 subjects who reported regular headaches was chosen at random from those with headache identified in a cohort of 46,244 employees of the French national power company aged between 35 and 50 years in 1989 participating in a yearly health survey. In 1993, all subjects were sent a headache questionnaire to complete and return. In 2003, an identical questionnaire was sent to all subjects who had returned exploitable data in 1993. Headache diagnosis was assigned retrospectively using the International Headache Society (IHS) criteria to migraine (IHS categories 1.1 and 1.2), migrainous disorder (IHS category 1.7), or other episodic headaches. ResultsOf 2500 subjects sampled, 2051 (82%) returned exploitable data for the first questionnaire in 1993. In 2003, 1250 (61%) of these provided a second data set. In 1993, 623 (30.4%) of subjects fulfilled diagnostic criteria for migraine. However, only 37% of these retained the diagnosis 10 years later. In contrast, the proportion of subjects with other forms of episodic headache rose from 23.7% to 31.6%. In 2003, 9.5% of the sample were headache-free. Retention or acquisition of a diagnosis of migraine was more common in women than in men, and age was associated with evolution to a less severe headache syndrome. In those subjects who continued to have headaches, frequency and severity were lower at the second assessment. ConclusionsOnly a minority of subjects diagnosed with migraine or migrainous disorder retain the diagnosis 10 years later, with most subjects evolving to a less disabling headache type.